Pengaruh Budaya Organisasi terhadap Niat berpindah Melalui Komitmen Organisasi pada PT. Pancaputra Mitratama Mandiri - Alyani, Kharina (Jurnal Ilmu Manajemen, 2020)
In this research, the authors explain the effect of organizational culture on turnover intention through organizational commitment (affective, continuance, and normative) at PT. Pancaputra Mitratama Mandiri. This study is using a quantitative approach. The population in this study amounted to 32 employees. Running research data using smartPLS (v.3.2.6) which uses SEM and PLS. Results of this study explain that organizational culture has a significant negative effect on turnover intentions, organizational culture has a significant positive effect on affective commitments, organizational culture has a significant positive effect on continuance commitment, organizational culture has a significant positive effect on normative commitment, affective commitment has a significant negative effect on turnover intentions, continuance commitment has no significant effect on turnover intentions, normative commitments has a significant negative effect on turnover intentions, and organizational commitment mediates the influence of organizational culture on turnover intention.